Formation and Development of the Italian Vocal School from 16th to 19th Centuries - Aleksandrovna Martynova, Yulia (2021)
The article is devoted to the development and formation of the Italian vocal schools in the era of the New Age. The most important aspects of the development of the Italian vocal school are the domination of castrate singers in the 18th century and their gradual ousting in the era of the romantic opera formation. During the 20th century, the internationalization of Italian opera and vocal teaching methods take place. The study is based on a complex of historical methods. The materials are of interest to researchers of vocal technology and cultural history.